Relay node placement to heal partitioned wireless sensor networks. (November 2015) - Ranga, Virender; Dave, Mayank; Verma, Anil Kumar
Highlights: Two naive approaches and two state-of-the-art heuristics are implemented along with our proposed solution to recover the lost connectivity of the partitioned WSN. The proposed solution considers a global zero gradient point inside the convex hull polygon. The proposed solution works perfectly for any number of disjoint segments. The proposed solution shows better performance compared to the other well-known state-of-the-art approaches. Abstract: The wireless sensor networks deployed in hostile environments suffer from a high rate of node failures. Such failures may convert a fully-connected sensor network into multiple disjoint sub-networks, leading to the network partition problem. The placement of relay nodes is the only way to restore the lost connectivity because these devices, compared to the sensor nodes, have a higher energy backup, with a longer communication range. In this paper, a new solution is proposed to heal the network partition problem in the wireless sensor network. The solution is based on a zero gradient point inside the convex hull polygon. The proposed solution is compared with various naive approaches, along with existing state-of-the-art solutions, that is, the Spider Web-1C heuristic and Steiner-minimum-tree based optimal relay node placement algorithm. The simulation experiment results confirm the effectiveness of our proposed approach.